THE RULE OF LAW IN THE CONTEXT OF THE EUROPEAN UNION’S WESTERN BALKANS ENLARGEMENT POLICY - Milena Apostolovska Stepanoska; Vasko Naumovski; Leposava Ognjanovska (Konrad Adenauer Foundation, Republic of North Macedonia Institute for Democracy “Societas Civilis”, Skopje, 2020)
The major project of European unifi cation that led to the creation of the European Union as a unique European construct was developed in a lengthy and multi-layered integration process. The creation and maintenance of peace and security in Europe after World War II is the raison d’être of this complex European integration process that was initiated with the foundation of the European Communities. The idea of peace was envisioned to be realised by means of economic integration of the member states, which would subsequently lead to mutual solidarity. The convergence of the member states’ economic policies implied the necessity to unify policies in other areas, too, which led to a spillover eff ect concerning integration beyond economy and a gradual development of political union as a following stage of integration. The European Union is actually the result of a unifi cation process based on certain values that set the ground for developing common policies to achieve common goals and realise common interests. In that context, the rule of law is recognised as one of the European Union’s basic values.1
Keywords: European Union